Kilka uwag dotyczących obostrzenia kary na podstawie art. 57a § 1 k.k. - Kmąk, Krzysztof (Wydawnictwo Uniwersytetu Wrocławskiego, 2021)
The paper presents selected issues regarding the aggravation of penalty for a misdemeanour of a hooligan character based on article 57a § 1 of the penal code. Considerations (including also polemic remarks) concern mainly the one appearing in article 57a § 1 of the penal code the concept of “lowest statutory penalty” and the possibility of applying in such cases article 37a and 37b of the penal code. Since a misdemeanour of a hooligan character is the ground for an extraordinary aggravation of the penalty, the work attempts to set the limits of criminal sanctions imposed with the application of article 57a § 1 of the penal code on the example of selected crimes.
Keywords: penal law; misdemeanour of a hooligan character; extraordinary aggravation of the penalty; statutory penalty; imposition of penalty